«RUSSKIY MIR» AS THE EFFECT OF «SUPPLEMENTED» REALITY - Пояркова, Т. К. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article reveals the subject of «Russian World» ideological concept’s attractiveness that is the mobilizing factor in the struggle against Ukraine not only for Russian citizens but for citizens of other countries. Different conceptions of «Russian World» are analyzed and their common grounds are highlighted. The main attention is paid to the role, which the idea of «Russian World» plays in the globalised epoch, where the net makes new bases to form social unity beyond the space and time. The author grounds the idea concerning the mobilization potential of «Russian World» conditioned by the ability to create the new solidarity, which will compensate the dramatic coincidence of military defeat, political humiliation, economic decline, cultural nihilism and general chaos.